Black Sapote Growing in the Florida Home Landscape - Jonathan H. Crane; Carlos F. Balerdi (EDIS)
Revised! HS1055, a 7-page fact sheet by Jonathan H. Crane and Carlos F. Balerdi, provides homeowners with a basic reference for growing canistel in the home landscape. Tables include cultural practices by month, fertilizer program and nutritional values. Published by the UF Department of Horticultural Sciences, October 2006.